DESENVOLVIMENTO DE PRODUTOS DE FORMA EFICIENTE NAS ORGANIZAÇÕES ATUAIS - Marlons Lino da Cruz; Antonio Marcos de Oliveira Siqueira; Israel Iasbik; José Damato Neto (The Journal of Engineering and Exact Sciences)
A B S T R A C T Due to market and technological competition, today's organizations they need tools that yield sufficient benefits for their growth. The objective of this research is to present the importance of product development efficient in today's organizations. For this, it is considered that products are developed to meet the needs. Therefore, it should be considered that customers have a perception of value and different costs of each other's products and also of the organization. Then it is necessary to market research, which is the responsibility of Marketing, which provides the information needed for product development. At this stage, product ideas are generated and developed. After being executed and linked to the market, the whole cycle must be managed the longer the product, the better for the organization. The use of tools such as 4P's (product, price, promotion and square) assist in making decisions about what, when, how much and where to produce that will ensure for the production and, mainly to the clients, improvement of the quality of the offered products. Efficient product development results in better products at lower costs, to be produced and intended for the consumer, increased profits, sales, customer loyalty and new ones.